P007 Improving paediatric chemotherapy prescribing through use of an electronic prescribing system. Issue 7 (19th June 2019) - Summerfield, Charlotte; Kafka, Susan; Lewis, Michelle; Makin, Guy; Williams, Joseph; Wood, Samuel
Abstract : Aim: Paediatric prescriptions are almost 50% more likely to contain an error than adult orders. The risk of prescription error is further increased when prescribing for malignant disease. 1 In 2017 the Trust introduced ChemoCare, an electronic prescribing system for paediatric chemotherapy. The primary aim of this study was to investigate whether implementing ChemoCare has affected the incidence and type of errors made in paediatric chemotherapy prescriptions, compared with written prescriptions. A secondary aim was to explore possible reasons why these prescribing errors may occur. Since 2014 it has been mandatory for all NHS England specialist trusts to send monthly submissions to the Systemic Anti-Cancer Therapy (SACT) Database, regarding the treatment of malignant disease in secondary care. 2 Therefore, the study also analysed Trust compliance with communicating treatment data to SACT. Methods: Data collection took place over a four-week period in Spring 2018. Prescriptions were reviewed by pharmacists and categorised as written or electronic. Prescriptions were then checked for 7 different error types; calculation error, drug prescribed on wrong day, incorrect drug prescribed for cycle, incorrect dose of concomitant medications, incorrect surface area used, not adjusted dose for previous age or weight related toxicities, no drug prescribed. The Fisher's Exact test was employed to detect significance between chemotherapy prescription type and error incidence. A written questionnaire was designed to obtain the views of consultants, pharmacists and specialist trainees, and explore possible reasons why prescription errors occur. ChemoCare treatment data was retrospectively reviewed in order to determine how many prescribed cycles had been marked as 'completed'. Results: 143 prescriptions were analysed. 34.4%(n=21) of written prescriptions contained errors, compared with 11.4% (n=5) of electronic orders. Two of the error types measured 'wrong calculation' and 'wrong drug prescribed for cycle' occurred significantly more frequently in written than electronic prescriptions. The Fisher's Exact test produced p values of 0.017 and 0.008 respectively. Of the 409 treatment cycles prescribed and administered on the electronic system, 56.5% (n=231) had not been marked as 'completed', so would not be returned to SACT as administered chemotherapy. Failure to communicate accurate chemotherapy data to SACT not only limits research opportunities to progress safety aspects of delivering chemotherapy, but also has significant cost implications for the Trust, as chemotherapy treatment costs are not recovered. Conclusion: This study supports the use of an electronic prescribing system for ordering paediatric chemotherapy, given the significant reduction in errors compared with written prescriptions. The introduction of a chemotherapy-specific safe prescribing poster is suggested in order to improve compliance with ChemoCare. Further studies analysing national compliance with data return to SACT, are required to identify cost implications for the NHS and subsequent areas for quality improvement. References: Avery AJ, Ghaleb M, Barber N, et al. Investigating the prevalence and causes of prescribing errors in general practice: The practice study. Pharmacoepidemiol Drug Saf 2012;21:4. NCRAS. Systemic Anti-Cancer Therapy Dataset [Internet]. [cited 2018 June 26]. Available from: http://www.ncin.org.uk/collecting_and_using_data/data_collection/chemotherapy